COPPER COINS OF THE PRINCIPALITY OF ANTIOCH (1103 – 1130): PHYSICO-CHEMICAL ANALYSIS - ORLYK, Vasyl; KROPIVNYI, Volodymyr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose and scientific novelty of the article. This article investigates the development of coin minting in the Crusader states, with a particular focus on the Principality of Antioch, during the first third of the 12th century. For the first time, the authors have conducted a comprehensive physicochemical analysis of copper coins from the Principality of Antioch, utilizing X-ray fluorescence spectroscopy, an MMP-2P model optical metallographic microscope, and a spark optical emission spectrometer Solaris CCD Plus GNR. Сonclusions. We conclude that the copper coins were struck on coin flans produced by casting. All the coins contain lead (Pb). Lead (Pb) was widely used in copper alloys in the Levant during the 11th–12th centuries. Taking into account the uniform technology used for producing flans for all coin types and the use of an alloy with a high lead (Pb) content, the authors conclude that a single mint operated in the Principality of Antioch. The consistent presence of lead (Pb) in all analyzed samples of Antiochene copper Crusader coins strongly suggests that lead was deliberately added during the melting process. After casting, the flans underwent further mechanical processing, including the removal of the solidified gating system and the remelting of defective pieces. Only then were the coins struck using a manual minting technique. A comparative analysis of the coins of the Principality of Antioch and those of the Seljuks of Syria indicates that the addition of lead (Pb) to the coin alloy was not a practice at the Antiochene mint prior to the Crusader occupation. Significant variations in the content of the primary elements in the coin alloy within a single coin type suggest the use of diverse raw materials in alloy production. Comparing the results of X-ray fluorescence spectroscopy and optical emission spectrometry, it is important to note that the former allows for more accurate determination of the chemical composition of a metal object, as the assessment is based on radiation from a larger surface area. Furthermore, X-ray fluorescence spectroscopy does not damage the surface of the studied coin. Keywords: Principality of Antioch, Crusades, Oriental coins, follis, fals, dirham, numismatics, coin minting, mint, physicochemical analysis.